The Effect of Self-Efficacy on Career Planning in Entrepreneurship of Adolescents - Adyanitama, Salsadirafi; Anggunani, Annisa Rizky; Prissianingsih; Yustitia, Amalia Dewi; Putra, Dwiki Nardian; Husna, Aftina Nurul (Urecol Journal. Part B: Economics and Business, 2023)
Entrepreneurship needs to be based on self-efficacy and careful career planning. Self-efficacy is defined as a person's belief about the ability to produce a specified level of performance in influencing their lives. Career planning is an activity or action to achieve career goals in accordance with the career direction that will be pursued including aspects of self-understanding, decision making, exploring, and preparing to enter the world of entrepreneurship. It is hypothesized that self-efficacy, both general self-efficacy and entrepreneurial self-efficacy, influence career planning in the field of entrepreneurship in adolescents. This study aims to test this hypothesis by conducting a survey involving 50 adolescents aged 15-18 years in Magelang. Data collection was carried out through online questioner consisting of the General Self-Efficacy Scale, the Entrepreneurial Self-Efficacy Scale, and the Entrepreneurial Career Planning Scale. Data analysis was carried out using Multiple Linear Regression Analysis using SPSS 25. As a result, there is an influence of independent variables both simultaneously and individually on the dependent variable (R = .913; R 2 = .834; F(2, 56) = 140.634; p <.00). The contribution of self-efficacy to career planning in the field of entrepreneurship is quite high, namely 83.4% indicating the importance of this variable. It is suggested that schools develop entrepreneurship education programs that strengthen skills, but also the self-efficacy so that adolescents has confidence in their capability to do entrepreneurship.